2020
DOI: 10.1016/j.heliyon.2020.e03996
|View full text |Cite
|
Sign up to set email alerts
|

Structuring biofilm communities living in pesticide contaminated water

Abstract: The wide use of pesticides in agriculture expose microbiota to stressful conditions that require the development of survival strategies. The bacterial response to many pollutants has not been elucidated in detail, as well as the evolutionary processes that occur to build adapted communities. The purpose of this study was to evaluate the bacterial population structure and adaptation strategies in planktonic and biofilm communities in limited environments, as tanks containing water used for washing herbicide con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 65 publications
0
16
0
Order By: Relevance
“…Aquatic environments are the final receptors for many xenobiotics including fipronil (FIP). Along the path between the application and the aquatic environment, physico‐chemical and biological changes can occur in a compound, and furthermore, its fate can be governed by these biological degradation and chemical decomposition (Lima et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Aquatic environments are the final receptors for many xenobiotics including fipronil (FIP). Along the path between the application and the aquatic environment, physico‐chemical and biological changes can occur in a compound, and furthermore, its fate can be governed by these biological degradation and chemical decomposition (Lima et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The tolerance evaluation of bacteria obtained in tanks containing washing water from pesticide containers ( Lima et al, 2020 ) showed that 67.2% of the isolates were sensitive to herbicides Boral ® and Heat ® at 15x and 45x concentrations. It is known that herbicides can be toxic for non-target organisms because of the electronegative characteristics of their active molecules ( Pileggi et al, 2020 ) and can reduce microbial diversity, such as that of Actinobacter in the presence of Granstar, a sulfonylurea herbicide, and that prior exposure to the herbicide acts as a selective agent ( Rachedi et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…CMA 6.9 was from the Collection of Environmental Microorganisms of the Laboratory of Environmental Microbiology of the State University of Ponta Grossa (UEPG). This collection consists of 67 bacterial biofilm isolates from water storage tanks used to wash agrochemical packaging ( Lima et al, 2020 ) at the BASF experimental station, Fazenda Escola Capão da Onça of UEPG.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The predicted metagenomics bioinformatics analysis was used in biofilm and planktonic communities in reservoirs containing herbicide-contaminated wastewater to characterize important genes, which functions were relevant for survival in these environments, by performing only 16S rDNA amplicon next-generation sequencing, and analyzing the genes present in the identified OTUs. With this technique it was possible to identify genes functions related to biofilm formation and structure, membrane transport, quorum sensing and xenobiotic degradation ( Lima et al., 2020 ).…”
Section: Bacterial Xenobiotic Responses By Omics-based Approaches Andmentioning
confidence: 99%